2007
DOI: 10.1159/000098528
|View full text |Cite
|
Sign up to set email alerts
|

Petrous Bone Langerhans Cell Histiocytosis Treated with Radiosurgery

Abstract: Langerhans cell histiocytosis (LCH) is a rare disease that may show as a solitary or multifocal lesion of bone, soft tissue or viscera. Involvement of the temporal bone has been described in 15–61% of patients with LCH, usually in association with multisystemic involvement. We report the case of a 30-year-old man presenting with vertigo and fluctuating hearing loss caused by monosystemic LCH of the left petrous bone. The patient was treated with radiosurgery (covering dose 10 Gy at 85% isodose, maximum dose 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…All 20 deaths occurred in patients with LettererSiwe disease. This finding confirms the number of organs involved is a key factor affecting the prognosis of LCH [11]. Among the patients with single-system bone LCH, The recurrence rate for multifocal bone involvement in the literature ranges from 12% [13] to 27.3% [1].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…All 20 deaths occurred in patients with LettererSiwe disease. This finding confirms the number of organs involved is a key factor affecting the prognosis of LCH [11]. Among the patients with single-system bone LCH, The recurrence rate for multifocal bone involvement in the literature ranges from 12% [13] to 27.3% [1].…”
Section: Discussionsupporting
confidence: 63%
“…Several modalities are used to treat the different presentations of the disease [9,11,14,20,21]. Local corticosteroid infiltration is frequently used in isolated bone lesions, with a reported remission rate of greater than 75% [7,22,28].…”
Section: Introductionmentioning
confidence: 99%
“…Anonsen et al reported that only 4 of 24 LCH cases of the head and neck involved the mastoid, and only one case involved the petrous bone. 1) Patients with petrous bone involvement may present with sensorineural hearing loss, 2,5,8) vertigo, 2,5,21) and facial nerve palsy. 2,4,8,20) Sensorineural hearing losses in previous cases have been chronic, 21) fluctuating, 5) or progressive, 8) whereas the present case showed sudden onset of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…1) Patients with petrous bone involvement may present with sensorineural hearing loss, 2,5,8) vertigo, 2,5,21) and facial nerve palsy. 2,4,8,20) Sensorineural hearing losses in previous cases have been chronic, 21) fluctuating, 5) or progressive, 8) whereas the present case showed sudden onset of hearing loss. Extension of the lesion to the skull base may cause palsy of other cranial nerves such as the abducens, [2][3][4]8,11,13) trigeminal, 4) optic, 11) and vagus 2) nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, these recommenda-tions could be extended by using modern methods of radiotherapy, such as intensity modulated radiotherapy (IMRT), but so far no cases treated with this technique have been described. There has been a report of a case of histiocytosis of the temporal bone pyramid treated with radiosurgery, where the tumour was irradiated with 10 Gy/isodose 85% and there was no recurrence of the disease within two years of follow-up [23]. Clinical studies show high radiosensitivity observed in LCH lesions and a favourable tumour response to low total dose [24].…”
Section: The Role Of Radiotherapymentioning
confidence: 99%